THE CORRELATION BETWEEN STUDENT’S ACHIEVEMENT IN VOCABULARY AND READING ABILITY OF THE TENTH-GRADE STUDENTS OF SMAN 1 BANGSAL - Sonya Brinda (Pimpinan Cabang Muhammadiyah Kramat Jati, 2021)
Vocabulary and reading are the most important aspects which have to be mastered by students in the middle of their English learning in class. Moreover, those two aspects are having a correlation to enhance their achievement in English comprehension besides writing and speaking. English learning in here has become a chance for the students to learn English as their foreign language. As we know, English as a foreign language is not an easy subject to be comprehended by students who have just learned it. Thus, students have to be more active and creative to create their own method to enhance their ability in English comprehension. This research was aimed to determine the correlation between students’ achievement in vocabulary and reading ability of the tenth-grade students at SMA 1 Bangsal. The research design was using the correlation design with the tenth-grade students as the population. When the research was conducted, the researcher only took some samples from tenth-grade students population by using the random sampling and found 75 students as the samples. Meanwhile, in collecting data process, the researcher has conducted the written test to find out the students’ achievement in vocabulary and reading ability. The data from tenth-grade students’ achievement was measured by Pearson Product Moment correlation formula, which become the analysis technique to evaluate a hypothesis concerning to the correlation between two variables that are examined statistically. The result showed that there is a significant correlation between students’ achievement in vocabulary and reading ability.